Array - Artanti, Frederica Jevita; Pujosusanto, Ari (LATERNE, 2024)
Video-Lektionen on the website de.islcollective.com is one of the learning media used at SMAN 15 Surabaya. Based on the researcher's observation in a class, it was found that most students understood the material taught using the media. This study was conducted to prove the effect of Video-Lektionen media on the de.islcollective.com website on student learning outcomes focused on listening skills. This research uses quantitative Quasi Experimental method with One Group Pre-test Post-test design. The population in this study were all students from class XII at SMAN 15 Surabaya. Meanwhile, the sample was taken with purposive sampling technique, namely all students of class XII MIPA 4 at SMA Negeri 15 Surabaya, totaling 36 students. The results of the N-Gain test using SPSS 29.0 calculating the pretest and posttest scores showed a score of 0.57 with a percentage of 58% which stated that the media used was quite effective. While the results of hypothesis testing assisted by SPSS 29.0 using the calculation of paired sample t-test obtained a significance of <.001 when decomposed into 0.000000034967 with a significance level of 5% (0.05) which states that the null hypothesis (H0) is rejected and hypothesis one (H1) is accepted which states that the Video-Lektionen media "Sommerferien - Perfekt" has a significant effect on student learning outcomes.